2021
DOI: 10.5920/bjpharm.836
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist-patient communication amid COVID-19 pandemic: A review of available options and potential impact

Abstract: Communication plays a vital role to ensure the safe and effective use of medicines. Nevertheless, movement restriction measures and social distancing policies amid the novel coronavirus disease 2019 (COVID-19) pandemic may have introduced a significant communication barrier between pharmacists and patients. As such, there is an urgent need for alternative approaches to continue pharmacist-patient communication for pharmaceutical care activities. This narrative review summarized the use of five alternative appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
2
5
0
1
Order By: Relevance
“…The respondents reported different levels of challenges in carrying out ward pharmacy duties. The highest-ranked perceived challenge was medical device counselling, consistent with the findings of other studies [ 5 , 9 , 12 , 17 ]. Social distancing, personal protective equipment (PPE), and the restriction of pharmacist entry into the ward during the COVID-19 pandemic introduced significant communication barriers between pharmacists and patients [ 5 , 9 , 12 , 17 ].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The respondents reported different levels of challenges in carrying out ward pharmacy duties. The highest-ranked perceived challenge was medical device counselling, consistent with the findings of other studies [ 5 , 9 , 12 , 17 ]. Social distancing, personal protective equipment (PPE), and the restriction of pharmacist entry into the ward during the COVID-19 pandemic introduced significant communication barriers between pharmacists and patients [ 5 , 9 , 12 , 17 ].…”
Section: Discussionsupporting
confidence: 87%
“…The highest-ranked perceived challenge was medical device counselling, consistent with the findings of other studies [ 5 , 9 , 12 , 17 ]. Social distancing, personal protective equipment (PPE), and the restriction of pharmacist entry into the ward during the COVID-19 pandemic introduced significant communication barriers between pharmacists and patients [ 5 , 9 , 12 , 17 ]. It hinders pharmacists' ability to demonstrate and reassess medical devices' use effectively.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The study by Jeminiwa et al demonstrated the effectiveness of eHealth in improving adherence to inhaled corticosteroids among patients with persistent asthma 13. Kilova et al addressed the prospects for ICT in providing OC and how eHealth related technologies had aided in the promotion of patient care during the outbreak of the epidemic 14 15. Another review by Iftinan et al primarily explored the eHealth services which could be used as an immediate alternative to PC for chronically ll patients during an epidemic 16…”
Section: Introductionmentioning
confidence: 99%